طريقة تحديد الحالة الحدّية المعبّرة عن إمكانية وصلاحية استمرار محركات الاحتراق الداخلي بالعمل ضمن الشروط الطبيعية - ديوب, محمد (Latakia University Journal -Engineering Sciences Series, 2018)
تركز البحث على إيجاد طريقة تخطيطية تعتمد على قياس ومراقبة المؤشرات الأساسية لمحركات الاحتراق الداخلي العاملة بالانضغاط (محركات الديزل) من أجل تحديد الحالة الحدية لعمل المحركات، والتي تحدد الزمن المتوقع لكي يتم إرسال المحرك لإجراء صيانة شاملة له، أو لبعض أجزائه الأساسية. تمّ أبضاً تحديد نسبة الاهتراء الحاصلة لأحد عناصر المحرك الأساسية، ولقد تمّ اختيار قطر الاسطوانة والاهتراء الذي يصيبها بهدف تحديد العمر الزمني للمحرك، وتحديد اللحظة الواجب إرسال المحرك فيها للصيانة الشاملة. من خلال مراقبة عدد كبير من المحركات التي وضعت في الإصلاح في المنطقة الصناعية بمدينة اللاذقية والتي عددها 30 محرك، من مختلف أنواع محركات الديزل والبنزين، وذات الاستطاعات المختلفة، لوحظ أن حوالي 15% من هذه المحركات لم يتم استغلال واستثمار كامل مدة العمل المصممة لأجلها، وأن حوالي 20% منها قد توقفت عن العمل بعد فترة ليست طويلة بسبب الاهتراء الشديد الذي أصاب أجزاء وقطع وميكانيزمات هذه المحركات مما أدى إلى تلفها وعدم استطاعتها القيام بعملها بشكل نظامي. وقد ساهم ذلك في زيادة استهلاك الوقود ومواد التزييت مما سيسبب لاحقاً ضرراً للاقتصاد الوطني. لقد أثبتت الطريقة التخطيطية المقترحة لتحديد الحالة الحدية للمحرك عند مقارنة النتائج التخطيطية مع نتائج الاختبارات العملية للمحركات فعاليتها ودقتها وبنسبة خطأ لم يتجاوز %6 مما يسمح بتطبيقها واعتمادها كطريقة فعالة لتحديد العمر الزمني الفعلي للمحرك ومقارنته مع العمر الزمني لاستثمار المحرك المنوه عنه في كتالوكات الشركة الصانعة وذلك عند ظروف تشغيل طبيعية ونظامية للمحرك. The research focuses on finding planning methods based on measuring and monitoring the basic indicators of internal combustion engines (Diesel engines) in order to determine the critical case of the engines, which determines the expected time for the engine or for some of its basic parts to be sent for comprehensive maintenance. The wear ratio of one of the basic components of the engine was also determined, we also chose the diameter of the cylinder and the corrosion that happens to it in order to determine the engine's lifetime and determine the moment when the engine should be sent for comprehensive maintenance. By observing a large number of engines put in repair in the industrial area in Lattakia, which are 30 engines of different types of diesel and gasoline, and with different capacities, it was noticed that about 15% of these engines were not exploited and invested the entire work period designed for them. Also it was noticed that 20% of them have stopped working because of the severe corrosion of parts, components and mechanics of these engines, which led to their damage and their inability to do their work on a regular basis. This has contributed to increased consumption of fuel and Lubricating materials, which causes damage to the national economy. The proposed planning method for determining the critical case of the engine when comparing the schematic results with the practical results of the engines has proved its efficiency and accuracy with an error rate of no more than 6% This allows it to be applied and adopted as an effective way to determine the actual lifetime of the engine and compare it with the life time of investing the engine mentioned in the manufacturer's catalogs when operating the engine under normal conditions.